2021
DOI: 10.2147/jir.s315281
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Analysis to Identify the Inflammatory Role of lncRNA Neat1 in Experimental Ischemic Stroke

Abstract: Background Ischemic stroke is one of the leading causes of mortality and disability worldwide. Following stroke, there is secondary neuroinflammation that promotes further injury. Identifying the long non-coding RNA (lncRNA) involved in neuroinflammation after cerebral ischemic stroke will promote the discovery of potential therapeutic targets. Methods We identified differentially expressed genes from genome-wide RNA-seq profiles of mice with focal ischemia using Gene O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Of these 15 studies, 5 on stroke, 6 on PD, 2 on spinal cord injury (SCI), and 1 on traumatic brain injury with the last one on epilepsy study, suggesting that it is sufficient to illustrate that Neat1 can modulate inflammation in the CNS disorders. Up on stroke condition, an upregulation of Neat1 was uncovered in ischemic stroke patients’ blood, 61 animals with an MCAO, 60 and in vitro cells with hypoxia. 50 Similarly, the upregulation of Neat1 has a detrimental effect and accelerates disease progression in PD via regulating inflammation.…”
Section: Neat1 Directly Regulates Inflammation In the Central Nervous Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 15 studies, 5 on stroke, 6 on PD, 2 on spinal cord injury (SCI), and 1 on traumatic brain injury with the last one on epilepsy study, suggesting that it is sufficient to illustrate that Neat1 can modulate inflammation in the CNS disorders. Up on stroke condition, an upregulation of Neat1 was uncovered in ischemic stroke patients’ blood, 61 animals with an MCAO, 60 and in vitro cells with hypoxia. 50 Similarly, the upregulation of Neat1 has a detrimental effect and accelerates disease progression in PD via regulating inflammation.…”
Section: Neat1 Directly Regulates Inflammation In the Central Nervous Systemmentioning
confidence: 99%
“… 123 , 131 , 132 Ni et al 62 exposed Neat1 knockdown BV-2 cells to oxygen–glucose deprivation/reoxygenation (OGD/R) and then detected the various levels of markers of M1 (CD16, CD32, and CD86) and M2 (BDNF, PDGF, and Arg-1) microglia, demonstrating that Neat1 knockdown suppresses M1microglial polarization but does not promote M2 microglial polarization. Jin et al 60 revealed that microglia had shorter ramifies and larger cell bodies after MCAO; however, the antisense oligonucleotides (ASO)-Neat1 group (Neat1 knockdown) was associated with significantly fewer activated microglia. Also, pyknotic nuclei and vacuolated cytoplasm were markedly reduced in the cortex and striatum of ASO-Neat1 mice.…”
Section: Neat1 Can Regulate the Activation Of Microgliamentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of ischemia, downregulation of H19 may reduce ischemic injury by inhibiting HDAC1 expression and thereby polarizing microglia to M2 type ( Wang et al, 2017 ). LncRNANEAT1 is also significantly expressed in ischemic stroke patients, and according to genome-wide RNA-seq studies, it may promote microglia activation ( Jin et al, 2021 ). Knockdown of lncRNA nuclear-enriched abundant transcript 1 (NEAT1) reduces the activity of the proinflammatory AKT/STAT3 pathway and inhibits microglia activation, reducing ischemia-reperfusion-induced injury ( Ni et al, 2020 ).…”
Section: Current Status Of Research On the Relationship Between Lncrn...mentioning
confidence: 99%
“…Recent studies have shown that lncRNAs, as endogenous small molecules, are extensively involved in the pathogenesis of ischaemic stroke [ 6 – 8 ]. A clinical study has found that the Rs217727 polymorphism of the lncRNA H19 gene is closely related to susceptibility to ischaemic stroke and can be used as a potential marker of ischaemic stroke [ 9 ].…”
Section: Introductionmentioning
confidence: 99%